2014
DOI: 10.1007/s12011-014-9978-7
|View full text |Cite
|
Sign up to set email alerts
|

Blood Serum and Seminal Plasma Selenium, Total Antioxidant Capacity and Coenzyme Q10 Levels in Relation to Semen Parameters in Men with Idiopathic Infertility

Abstract: In this case-control study, we aimed to evaluate the serum and seminal plasma levels of Selenium (Se), total antioxidant capacity (TAC), and Coenzyme Q10 (CoQ-10) and determine their relationship with sperm concentration, motility, and morphology in men with idiopathic infertility. A total of 59 subjects were enrolled in the study. Forty four patients were diagnosed with idiopathic male infertility and had abnormal sperm parameters, and 15 subjects had normal sperm parameters with proven fertility. Serum Se, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 33 publications
3
39
1
2
Order By: Relevance
“…An alternative approach is to measure TAC of seminal plasma which is simple and cost‐effective. The determination of seminal TAC has been proven to be relevant in humans for fertility assessment (Eroglu et al., ; Khosravi et al. 2104).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative approach is to measure TAC of seminal plasma which is simple and cost‐effective. The determination of seminal TAC has been proven to be relevant in humans for fertility assessment (Eroglu et al., ; Khosravi et al. 2104).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach is to measure TAC of seminal plasma which is simple and cost-effective. The determination of seminal TAC has been proven to be relevant in humans for fertility assessment (Eroglu et al, 2014;Khosravi et al 2104). In the current study, we measured seminal TAC level and found that TAC of high-fertile bulls was significantly higher than that of subfertile bulls and positively correlated with bull fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Selenium (Se) is a trace element with strong antioxidant and anti-inflammatory properties and reduces the risk of cancer, including prostate cancer (Christensen 2014). Infertile men have lower Se concentrations in seminal plasma, and positive correlations exist between sperm parameters and serum Se levels (Eroglu et al 2014;Turk et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, deficits in antioxidant capacity may important in the etiology of ASD. The total antioxidant capacity (TAC) in urine and plasma is a parameter used to characterize the antioxidant status of the body [8,9]. Recent studies in ASD have shown significantly reduced urinary levels of TAC, indicating increased vulnerability to oxidative damage [6], and significantly higher urinary levels of 8-hydroxy-2′-deoxyguanosine (8-OHdG) [10].…”
Section: Introductionmentioning
confidence: 99%